2017
DOI: 10.1080/19338244.2017.1339011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of acute occupational pesticide exposures reported to poison control centers in Texas, 2000–2015

Abstract: In the United States, there is limited literature on occupational pesticide exposures despite being associated with adverse health outcomes, including in large states such as Texas. The purpose of this article is to characterize occupational pesticide poison center exposures in Texas. Descriptive statistics were used to describe exposures (eg, exposure routes, type of pesticide, medical outcome, clinical effects, and temporal/seasonal patterns). From 2000 to 2015, there were 2,303 occupational pesticide poison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Data from the NEISS-Work 1 were used to identify nonfatal civilian occupational inhalation injury cases treated in US hospital EDs from 2014 to 2017. The National Institute for Occupational Safety and Health (NIOSH), in collaboration with the Consumer Product Safety Commission, collects surveillance data on work-related nonfatal injuries and illnesses treated in US hospitals with a 24-h ED.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the NEISS-Work 1 were used to identify nonfatal civilian occupational inhalation injury cases treated in US hospital EDs from 2014 to 2017. The National Institute for Occupational Safety and Health (NIOSH), in collaboration with the Consumer Product Safety Commission, collects surveillance data on work-related nonfatal injuries and illnesses treated in US hospitals with a 24-h ED.…”
Section: Methodsmentioning
confidence: 99%
“…The occupational health surveillance systems that do exist in the United States often do not enforce reporting requirements, are limited to a few states, and may not include the full range of inhalation cases. Various surveillance efforts to identify the prevalence of inhalational injuries have used poison control centers, physician reports, hospital discharge records, and hospital emergency department (ED) records 1–3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In performing these tasks, the PICs gather data regarding exposures such as chemical and exposure route. Such data have been used to investigate occupational exposures to specific product groups such as pesticides , and hand sanitizers, or population groups such as adolescent workers. The Swedish PIC serves the whole Swedish population (10 million inhabitants) and receives approximately 80,000 calls concerning human exposures annually. About 1 in 10 calls concern children 10–19 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Overviews of injuries and incidents provide an important basis for injury prevention and may identify problematic uses of chemicals or groups at risk. Data from calls made to poisons information centres have been used to investigate chemical injuries in schools [1,2] and in the workplace [3][4][5][6][7] as well as for specific target groups such as pesticide exposures [8], workers in small enterprises [9], military personnel [10] and adolescent workers [11][12][13]. A recent comparison between the occupational cases found in the Swedish Poisons Information Centre (PIC) database and the official statistics of the Swedish Work Environment Authority (SWEA) showed that these two data sources reveal somewhat different pictures of chemical accidents at work [7].…”
Section: Introductionmentioning
confidence: 99%